Analysis of the Effectiveness of M-Tax in Providing Certificate Services (PP 23) for North Bekasi Di KPP Pratama Umkm Taxpayers - Safitri, Risqy Indah (Data : Journal of Information Systems and Management, 2023)
In this digital era, tax has an online-based application called m-tax. M-Taxes is a mobile application-based jasa.go.id site portal. DJP stated that the m-tax application was developed to make it easier for taxpayers to get more personal, easy and fast services via cellphone. Objective: To analyze m-tax in providing Certificate Services (PP 23) at KPP Pratama North Bekasi based on an analysis of effectiveness, obstacles faced and efforts made to overcome obstacles. Method: This research is qualitative descriptive. Data collection using observation, documentation and interviews. Results: That m-tax in providing Certificate Services (PP 23) at North Bekasi KPP Pratama is still not effective because there are still many taxpayers who do not know about the m-tax application due to the lack of information and outreach provided, this is based on achieving the goal , integration and adaptation. The obstacle faced is that socialization is not comprehensive enough because there are still many taxpayers who lack information so that the majority of taxpayers do not use the m-tax application to obtain a Certificate (PP 23). Efforts must be made to carry out comprehensive outreach so that taxpayers can get good information.